Rancang Bangun Sistem Informasi dan Pengolahan Data Kelahiran, Kematian, Datang, dan Pindah di Kantor Kelurahan Sekaran Kecamatan Gunungpati Kota Semarang - Sari, Rini Kartiko; Sunardiyo, Said; Putri, Riana Defi Mahadji (Edu Komputika Journal, 2016)
This research aims to design, develop, and apply the information systems and data processing of birth, death, come, and have now moved in the Village Office Gunungpati District of Semarang. The method used in this study is a Rapid Application Development (RAD), which has a cycle of planning requirements, software design, inplementasi, and testing. The testing phase of this research is done with black-box testing and user trials. Black-box testing focuses on functional requirements, while the user test carried out by village officials in the office klurahan sekaran. The tools used in this study is a sheet instruments. From the data analysis, the result is that village officials at the Village Office have now proved that Information Systems birth, death, come, and moved very easy to use and can help the task of village officials in providing services to the community have now. This is indicated by the results of testing black-box testing and test users who say that the system is fit for use with both and facilitate service to the community. Suggestions based on the information system of birth, death, come, and move that has been so is that these letters can be printed exactly to the letter from the Office of the City Government of Semarang.